Race and Employment: The Historical Case of Head Coaches in College Basketball - Nesseler, Cornel; Gomez-Gonzalez, Carlos; Dietl, Helmut; del Corral, Julio (Frontiers in Sociology, 2020)
This study analyzes how the number of Black coaches in college basketball has evolved since 1947. The analysis puts a focus on the time period after 1973 when regulatory requirements changed and a new Division was established. The change in the number of Divisions created distorted conditions and led to a significant difference in the number of Black coaches within Divisions. We trace a significantly lower number of Black coaches in Division 3 which is still visible 40 years later. The results are time consistent, not clustered geographically, and unrelated to specific institutions. Our results have policy implications for college sports as well as other industries with similar working conditions.